In the shadow of ‘village cathedrals’. Sacred wooden architecture from the area of Sandomierz and Kielce dioceses at the turn of the 19th and 20th centuries based on selected examples - Rutkowska-Siuda, Daria (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
In the early nineteenth century wooden architecture prevailed in the area of the Kingdom of Poland. It also dominated in sacral architecture. This article focuses on the analysis of selected examples of Roman Catholic churches from the area of Sandomierz and Kielce dioceses. Objects from, inter alia, Dzierzgów, Miedzierza, Policzna, Olbierzowice, Kielce, Zborówek, allow us to observe a wide spectrum of problems affecting this type of building: from attempts to protect it by the transformation, which often deprived it of the historic value, to the complete replacement with brick buildings, in which shadow it had to pass away. To better understand some of the formal transformations of the mass and the types of work carried out, source descriptions from archival documentation and periodicals are cited.